Pulsed Field Ablation of Superior Vena Cava: Feasibility and Safety of Pulsed Field Ablation - Zhu, Tongjian; Wang, Zhen; Wang, Songyun; Shi, Tiancai; Zhu, Xiaolin; Ma, Kezhong; Wang, Zhuo; Gao, Jinnian; Jiang, Hong (Frontiers in Cardiovascular Medicine, 2021)
Background: Studies have shown that pulsed field ablation (PFA) has excellent effectiveness and safety in pulmonary vein isolation (PVI). However, there are few reports about the application of PFA, especially the alternating current (AC) biphase PFA, in superior vena cava (SVC) isolation, and its effectiveness and safety are still unclear. Objective: To investigate the efficacy and safety of the AC biphase PFA for SVC isolation, and to provide evidence for the clinical use of PFA for SVC. Methods: Eight pigs and two dogs were included in the study. PFA was delivered to these pigs and dogs. Pacing threshold and electrogram data were recorded before and after PFA. Voltage mapping of SCV was obtained before, after, and 3 weeks after PFA. At the end, all animals were euthanatized for gross pathology analysis. Results: For eight pigs, the median pacing threshold was 1.5 (1.4, 2.75) mA before PFA, while > 6.0mA after PFA for all animals. The average electrogram amplitude reduction was 61.33% ± 24.90% for ablations with the initial amplitude≥0.5mV. For two dogs, pacing threshold change and electrogram amplitude reduction were also observed. No phrenic palsy or sinus node injury was observed during PFA in any animal. Furthermore, voltage mapping showed that the voltage amplitude was significantly decreased in all animals and this could be kept for more than 3 weeks. Moreover, transmural tissue damage with reserved vessel and nerve were shown, no SVC stenosis was found at 3 weeks after PFA. Conclusion: PFA can effectively isolate SVC. Transmural tissue damage of SVC can be achieved without phrenic palsy, sinus node injury nor SVC stenosis.